2020
DOI: 10.4269/ajtmh.20-0458
|View full text |Cite
|
Sign up to set email alerts
|

A University-Wide Preparedness Effort in the Alert Phase of COVID-19 Incorporating Community Mental Health and Task-Shifting Strategies: Experience from a Bornean Institute of Higher Learning

Abstract: The COVID-19 pandemic caught the world by surprise, causing millions of confirmed cases and hundreds of thousands of deaths. Hence, the Malaysian government announced a Movement Control Order at the start of the containment phase to flatten the epidemiological curve. Universiti Malaysia Sabah (UMS), a public university in Borneo, was accelerated into alert phase because of high risk of case importation from more than 400 China incoming undergraduates. Measures to mitigate the potential COVID-19 outbreaks in it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…In addition, previous study observed that during the early period of COVID-19 pandemic, majority of online information regarding COVID-19 were coming from non-reliable resources and poor quality information without scientific support [16]. Therefore, it is very important to ensure that students are specifically catered to have adequate knowledge that will influence their self-prevention habits that will at the end of the day help curb the spread if COVID-19 infection [6], [7]. Besides that, it may have psychological effects on those students who are currently being emotionally disturbed by the movement control order implementation [17]- [19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous study observed that during the early period of COVID-19 pandemic, majority of online information regarding COVID-19 were coming from non-reliable resources and poor quality information without scientific support [16]. Therefore, it is very important to ensure that students are specifically catered to have adequate knowledge that will influence their self-prevention habits that will at the end of the day help curb the spread if COVID-19 infection [6], [7]. Besides that, it may have psychological effects on those students who are currently being emotionally disturbed by the movement control order implementation [17]- [19].…”
Section: Discussionmentioning
confidence: 99%
“…This is because new standard operational procedure needed to be established to take care of students especially those who were staying in campus Nevertheless, even before MCO, the institute had already been put on alert phase, and the operational team worked vigilantly to control and prevent any contact between campus residents and outsiders to reduce the risk of transmission. 7 Individual with high risk criteria such as fever, symptoms and travelling history were barred from entering the institute. Prevention measures were forwarded to all faculties in order to ensure social distancing was practised and disinfection steps were conducted at their premise.…”
Section: Discussionmentioning
confidence: 99%
“…5 With such potential for Covid-19 spread in mind, the university has implemented several steps in preparedness even since the alert phase to prevent any COVID-19 infections and emergence of clusters. 7 In China, as of 11 th February 2020, around sixtytwo percent of individuals confirmed for COVID-19 were drawn from nearly 70,000 suspected cases. The majority of them were from the working age group (87%), who mobilized freely and reported to have milder symptoms (81%).…”
Section: Introductionmentioning
confidence: 99%
“…Such prolonged quarantine can no doubt result in increased fears of Covid-19 (21,22), and have been associated with depression, anxiety, and stress in similar populations (23)(24)(25). Hence, it is crucial that early preventative measures at the university level be undertaken to increase surveillance at the alert phase (26,27), especially taking into account the impact of digital learning on student burnout and mental health (28). Crucially, brief psychological interventions also need to be undertaken to reduce psychological morbidity, especially in rural areas (29,30).…”
Section: Discussionmentioning
confidence: 99%